Estudo analítico de constituintes majoritários de óleos essenciais por espectroscopia Raman - Martins, Quesle da Silva (2016)
The analytical study of constituents of essential oils by Raman spectroscopy seeks to present a consistent approach to the vibrational activity presented in this type of material. Essential oils have aroused great interest of the industry in general by its various applications, such as the food industry has the requisite interest in aspects for their antioxidant and antimicrobial activity that has been shown. This paper presents a theoretical discussion from the application and results of calculations from first principles (ab-initio) so that the acquired data can be compared with experimental results of the proposed measures. Thus, essential oils were subjected to analysis by monochromatic source of Raman spectroscopy with 633nm excitation frequency. The identification of the major components were obtained by physical and chemical processes and after this identification, their molecular structures were subjected to DFT calculations. At the end they are shown the spectral structure of the measured and calculated oils and their major components followed by a behavioral interpretation of spectra relating to the molecule considered here as the primary structure of the essential oils. So it followed in order to provide a deepening of Raman spectroscopy for the study and analysis of essential oils from different nature.